Eksplorasi Pelaksanaan Praktikum Fisika SMA Di Kota Ambon dalam Masa Pandemi Covid 19 - Limba, Anatasija (INSTITUT AGAMA ISLAM NEGERI AMBON, 2022)
Practicum in learning physics in the special conditions of the COVID-19 pandemic towards the new normal era can be done both online and offline. The fact shows that the description of the implementation of practicum in high school physics learning in Ambon City during the Covid-19 pandemic does not yet exist. The purpose of this study was to explore the implementation of practicum in high school physics learning in Ambon City during the Covid-19 pandemic as a whole, starting from planning, implementation and practicum results. The results of the exploration are used as the basis for formulating policy recommendations for planning, implementing and evaluating practicum in high school physics learning in Ambon City in the new normal era. Exploration was carried out by distributing questionnaires and conducting interviews with 71 teachers. The results of the exploration showed that the planning, implementation and assessment of practicum activities in high school physics learning during the Covid 19 pandemic did not go well. For this reason, it is recommended that training be carried out as soon as possible regarding the planning, implementation and assessment of practicum in physics learning both online and offline so that teachers are ready to carry out practical activities in physics learning to enter the new normal. Keywords: Exploration, Practice, Physics, SMA, Ambon City